2015
DOI: 10.1097/mao.0000000000000535
|View full text |Cite
|
Sign up to set email alerts
|

The Rising Incidence of Spontaneous Cerebrospinal Fluid Leaks in the United States and the Association with Obesity and Obstructive Sleep Apnea

Abstract: The national rate of craniotomy for spontaneous CSF leak repair is rising. This condition is yet another public health problem related to the rising obesity epidemic. All patients with spontaneous CSF leaks should be evaluated for OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
158
2
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(170 citation statements)
references
References 14 publications
8
158
2
2
Order By: Relevance
“…Unlike traumatic or iatrogenic leaks, sCSF leaks are highly associated with obesity and idiopathic intracranial hypertension (IIH). The obesity epidemic in the US started in the 1980s and after a 1–2 decade delay, there has been a corresponding rise in the number of patients with sCSF leaks . Spontaneous CSF leaks do not typically self‐resolve, and require surgical repair.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike traumatic or iatrogenic leaks, sCSF leaks are highly associated with obesity and idiopathic intracranial hypertension (IIH). The obesity epidemic in the US started in the 1980s and after a 1–2 decade delay, there has been a corresponding rise in the number of patients with sCSF leaks . Spontaneous CSF leaks do not typically self‐resolve, and require surgical repair.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the reports did not correlate the severity of OSA with polysomnography, nor was it offered to patients with OSA symptoms (snoring, excessive daytime sleepiness, and fatigue). [6][7][8]11 The lack of formal polysomnograms in all patients with spontaneous CSF leaks may have underestimated the incidence of OSA.…”
Section: Discussionmentioning
confidence: 98%
“…Nowadays CSF fistulae are said to be of rising incidence and one study has shown that there is a twofold rise in the incidence of CSF rhinorrhoea in United Kingdom from 2002 to 2012 [6] This could be partly due to the increasing awareness among the medical professionals.…”
Section: Discussionmentioning
confidence: 99%
“…[2] According to the American rhinology society the causes for CSF rhinorrhoea can be classified as Traumatic, accidental traumatic or iatrogenic, tumour related and spontaneous. [2] Most of the scholarly articles have defined spontaneous CSF rhinorrhoea as an entity where the cause for the problem is not clear. However recently there are discussions that majority of the people classified as spontaneous CSF rhinorrhoea could be having intracranial hypertension.…”
Section: Introductionmentioning
confidence: 99%